PUBLIC DELIBERATION, DISCURSIVE PARTICIPATION, AND CITIZEN ENGAGEMENT: A Review of the Empirical Literature - Carpini, Michael X. Delli; Cook, Fay Lomax; Jacobs, Lawrence R. (Annual review of political science, 2004)
▪ Abstract  Many theorists have long extolled the virtues of public deliberation as a crucial component of a responsive and responsible democracy. Building on these theories, in recent years practitioners—from government officials to citizen groups, nonprofits, and foundations—have increasingly devoted time and resources to strengthening citizen engagement through deliberative forums. Although empirical research has lagged behind theory and practice, a body of literature has emerged that tests the presumed individual and collective benefits of public discourse on citizen engagement. We begin our review of this research by defining “public deliberation”; we place it in the context of other forms of what we call “discursive participation” while distinguishing it from other ways in which citizens can voice their individual and collective views on public issues. We then discuss the expectations, drawn from deliberative democratic theory, regarding the benefits (and, for some, pitfalls) assumed to derive from public deliberation. The next section reviews empirical research as it relates to these theoretical expectations. We conclude with recommendations on future directions for research in this area.